Insight into the Fermentation of Chinese Horse Bean-chili-paste. Issue 7 (3rd October 2021) - Lu, Yunhao; Yang, Linzi; Yang, Guohua; Chi, Yuanlong; Sun, Qun; He, Qiang
ABSTRACT: Chinese horse bean-chili-paste (CHCP) is a very popular semi-solid condiment with centuries of history in southwestern China. The consumption and international trade have ascended sharply in the past few years; CHCP industry, however, is facing the challenges of modernization and standardization for the product quality and safety. In the current review, an overview of the traditional fermentation procedures and characteristics, together with the present research progress on flavor chemistry, microbial diversity and succession, and mycotoxin detection and control methods of CHCP is presented. Furthermore, application techniques and requirements for future study needs and industrial improvement are proposed. Here, the detailed and systematic review could lay a foundation for conferring enhanced organoleptic attributes, improving food safety, and also achieving intelligent production.